Dzień Spółdzielczości w Pelplinie. (Gniew : [s.n.], 1947)
Afisz z programem uroczystości, które miały miejsce 28.09.1947 r.
Keywords: Pelplin (Polska) -- 1945-1970 -- druki ulotne; Pelplin (Polska) -- 1945-1970 -- plakaty